Pengaruh Rasio Panjang dan Diameter Pipa Suplai terhadap Unjuk Kerja Model Pompa Tanpa Motor (Hydraulic Ram Pump) - Jorfri B Sinaga (JURNAL MECHANICAL, 2011)
A hydraulic ram pump is environmentally friendly devices using the energy from a stream of water falling from a low head as the driving power to pump part of the water to a head much higher than the supply head for agricultural or domestic use. In the use of this pump, one of factors that influence the performance is ratio of drive pipe length to diameter (L/D). This paper presents the experimental study of effect of ratio of drive pipe length to diameter on hydraulic ram pump designing model. This hydraulic ram pump designing model is tested on various ratio of drive pipe length to diameter, namely 158, 165, 176, and 202. The results of the testing of the model hydraulic ram pump shows that the operation of this pump should  use the ratio of drive pipe length to diameter (L/D) of 176. Using supply head of 1 m and volume of air chamber of 5702,754 cm3, water can be pumped with the volume flow rate of 3 lit/min to the height of  8,5 m, and the efficiency of this pump is 78,7  %. The data of the testing results also show that using the volume of air chamber of 4562,203 cm3, and supply head of 1 m, this model of hydraulic ram pump can lift water of 2,727 lit/min  to the height of 9,5 m with the maximum efficiency of 87,96 %..